Why God Became Man: From Text to Sermon on Hebrews 2:5–18 - Miller, Donald G. (Interpretation, 1969)
The Incarnation and the Cross—these were the two problems that offended the first readers of the epistle. And they remain the scandal for us moderns—the scandal which guarantees that what we hear is indeed the gospel.